Barriers and facilitators of physical activity in adolescents with intellectual disabilities: An analysis informed by the COM‐B model. Issue 3 (28th February 2022) - McDermott, Gary; Brick, Noel E.; Shannon, Stephen; Fitzpatrick, Ben; Taggart, Laurence
Abstract: Background: Adolescents with intellectual disabilities are insufficiently physically active. Where interventions have been developed and delivered, these have had limited effectiveness, and often lack a theoretical underpinning. Aim: Through application of the COM‐B model, our aim is to explore the factors influencing adolescent physical activity within schools. Methods: A qualitative methodology, using focus groups with students who have mild/moderate intellectual disabilities, their parents'/carers' and teachers'. The COM‐B model provided the lens through which the data were collected and analysed. Results: We identified of a range of individual, interpersonal, and environmental factors influencing physical activity, across all six COM‐B constructs, within the context of the 'school‐system'. Conclusion: This is the first study to use the COM‐B model to explore school‐based physical activity behaviour, for adolescents with intellectual disabilities. Identification of such physical activity behavioural determinants can support the development of effective and sustainable interventions.